Faculty and Student Online Experiences Amidst the COVID-19 Pandemic: A Descriptive Study (Part 1) (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2022)
Background: With the declaration of a global pandemic in March 2020, post-secondary institutions closed campuses, learner clinical experiences were suspended, and teaching moved to a fully online format. Prior to data collection, a literature review yielded few results beyond editorials, student and faculty reflections, and blog postings in relation to COVID-19. It is crucial that we learn from the experience of students and faculty to evaluate the novel teaching and learning realized during the pandemic and prioritize a scholarly plan including potential innovative approaches for future educational programming.Objectives: The overall goal for this multi-site research was to capture the perspectives of nursing students, and nursing faculty members on their teaching and learning experiences online during a declared pandemic and provincial state of emergency.Design: Descriptive survey study.Setting: Online environment in one province in Eastern Canada.Participants: Nursing students and faculty in three Canadian bachelor of science in nursing programs during the spring and summer semester 2020.Method: Participants were invited via email to complete an online survey (via Opinio) related to their experience of learning or teaching in the fully online environment.Results: Quantitative data were analyzed using descriptive (frequencies, means, modes) statistics to describe the experience from the participants’ perspectives and inferential (Chi-square test, t-test) statistics to investigate perceptual differences between the faculty members’ and the students’ perspective related to the effectiveness, engagement, and comfort in the online learning and teaching experience. Qualitative data were analyzed using thematic analysis. The focus of this article is the presentation and discussion of the quantitative data.Conclusions: The resulting knowledge provides an in-depth understanding of the fully online learning and teaching experience during a global pandemic that is invaluable to inform future program planning in relation to online learning and teaching in a practice profession.